Balanced strength and ductility in CNT/Al composites achieved by flake powder metallurgy via shift-speed ball milling. (May 2017) - Xu, Run; Tan, Zhanqiu; Xiong, Dingbang; Fan, Genlian; Guo, Qiang; Zhang, Jie; Su, Yishi; Li, Zhiqiang; Zhang, Di
Graphical abstract: Abstract: Flake powder metallurgy via shift-speed ball milling (SSBM) was proposed to combine the mechanisms of low-speed and high-speed ball milling (LSBM and HSBM) for carbon nanotube (CNT)-reinforced, strong and ductile aluminum composites. LSBM featured mild ball-to-powder collision and slow flattening of spherical Al powders into flakes, leaving enough time for CNTs to be uniformly dispersed on the surface of Al flakes and causing little damage to CNTs; HSBM featured much stronger collision and cold welding of Al flakes, leading to clustered CNTs within the welded Al particles with serious damage but better inter-flake bonding. Therefore, the coordination of CNT dispersion, integrity and interfacial bonding could be achieved by a smart powder processing of SSBM, namely a longer starting LSBM and a shorter following HSBM. As demonstrated, such SSBM resulted in comparable strength in 1.5 wt.% CNT/Al composites but doubled and tripled ductility as those fabricated via LSBM and HSBM.